The Impact of Tourism on Economic in North Sulawesi: Input-Output Analysis Perspective - Siswahto, Eko; Muryani, Muryani (Universitas Airlangga, 2020)
The North Sulawesi Tourism Sector is a tourism rising star in Indonesia with a 600% growth of foreign tourists visiting North Sulawesi. The growth of tourists will encourage the growth of tourist expenditure which will have an impact on the economy. Research on the impact of tourism on the economy has been carried out. In general, research on the economic impact of tourism activities uses a sector approach related to tourism economic activities such as hotels, restaurants, transportations, and recreational activities sectors. This study uses an approach by forming the tourism sector independently to obtain the results of a more accurate calculation and analysis of the economic impact of the tourism sector. Input-Output Analysis is used as an instrument of linking and multiplier analysis of outputs and incomes of the people of North Sulawesi in 2018. Linkage analysis (forward and backward linkage) shows that the tourism sector in the economy of North Sulawesi is a key sector. The output multiplier and income multiplier are created by tourist expenditure in 2018 are 1.83 for the multiplier output and 1.88 for the multiplier income. With a tourist expenditure of 4.56 trillion rupiahs in 2018, it will create an economic output of 8.38 trillion rupiahs and create an income of 1.28 trillion rupiah. Keywords: Tourism, Economic Impact, North Sulawesi, Multiplier Analysis, Input-Output Analysis JEL: C67, R11, Z32